Prevalence of Urinary Incontinence in School Going Children: A Cross-sectional Study - Shrestha, Nistha; Sahukhala, Salina; K.C, Diva; Sandalcidi, Dawn; Adhikari, Shambhu Prasad (Journal of Nepal Health Research Council, 2021)
Background: Urinary incontinence is a highly prevalent condition that affects both gender across the age span and has significant social and psychological impact. The objective of this study was to determine the prevalence of urinary incontinence in school going children and assess the association of Incontinence Symptom Index-Pediatrics with age and gender.Methods: A cross-sectional study was carried among 305 children aged 11-16 years using convenient sampling in a school of Dhulikhel municipality. Data were analysed using descriptive analysis and spearman’s correlation coefficient.Results: Prevalence of stress, urge and nocturnal enuresis were 22.95%, 19.34% and 3.93% respectively. Gender was significant with stress (p>0.001) and urge (p>0.039) incontinence whereas age was significant with nocturnal enuresis.Conclusion: The episode of Urinary incontinence is common in school going children. It’s important that children, parents, teachers and medical practitioners be aware of these phenomena. Keywords: Children; prevalence; urinary incontinence